Antisecretory factor in severe traumatic brain injury (AFISTBI): protocol for an exploratory randomized placebo-controlled trial - Linus Réen; David Cederberg; Niklas Marklund; Edward Visse; Peter Siesjö (Trials)
Abstract Background Despite recent advances in neuroimaging and neurocritical care, severe traumatic brain injury (TBI) is still a major cause of severe disability and mortality, with increasing incidence worldwide. Antisecretory factor (AF), commercially available as Salovum®, has been shown to lower intracranial pressure (ICP) in experimental models of, e.g., TBI and herpes encephalitis. The aim of this study is to assess the effect of antisecretory factors in adult patients with severe TBI on ICP and inflammatory mediators in extracellular fluid and plasma. Methods/design This is a single-center, randomized, placebo-controlled clinical phase 2 trial, investigating the clinical superiority of Salovum® given as a food supplement during 5 days to adults with severe TBI (Glasgow Coma Scale (GCS) < 9), admitted to the neurocritical intensive care unit (NICU) at Skane university hospital, Lund, Sweden. All patients with GCS < 9 and clinical indication for insertion of ICP-monitor and microdialysis catheter will be screened for inclusion and assigned to either the treatment group (n = 10) or placebo group (n = 10). In both groups, the primary outcome will be ICP (mean values and change from baseline during intervention), registered from high-frequency data monitoring for 5 days. Secondary outcomes will be inflammatory mediators in plasma and intracerebral microdialysis perfusate days 1, 3, and 5 during trial treatment. Trial registration ClinicalTrials.gov NCT04117672. Registered on September 17, 2017. Protocol version 6 from October 24, 2023.